Given :
The local approximation to the function g at x = 1/2 is y = 4x+1.
To Find :
The value of g(1/2) + g'(1/2).
Solution :
It is given that at g( y ) = 3x + 1 , at x = 1/2.
Differentiating g( y ) w.r.t x ,we get :
g( y )' = 3
So, g( y ) + g( y' ) = 3/2 + 1 + 3
g( y ) + g( y' ) = 11/2
Hence, this is the required solution.
True or False:
2.4 ÷ 0.6 =
0.04 x 6 =
Answer:
false
Step-by-step explanation:
Can someone please answer my question Geometric Sequence:
3, 6, 12, 24, …
Answer:
48
Step-by-step explanation:
You multiply by 2 each time
I believe it is multiplying by 2 each time.
3 x 2 = 6
6 x 2 = 12
12 x 2 = 24
So if this was true to continue we would just multiply by 2....
24 x 2 = 48
48 x 2 = 96
96 x 2 = 192
192 x 2 = 384
384 x 2 = 768
and continue for as long as you need to go....
Hope this helped!Y=sqrt(x)(8x-5) find the derivative
Answer:
[tex]\displaystyle y' = \frac{24x - 5}{2\sqrt{x}}[/tex]
General Formulas and Concepts:
Algebra I
Exponentials [Fractions] - Are radicalsExponential Rule [Rewrite]: [tex]\displaystyle b^{-m} = \frac{1}{b^m}[/tex]Calculus
Derivatives
Derivative Notation
Derivative of a constant is 0
Basic Power Rule:
f(x) = cxⁿ f’(x) = c·nxⁿ⁻¹Product Rule: [tex]\displaystyle \frac{d}{dx} [f(x)g(x)]=f'(x)g(x) + g'(x)f(x)[/tex]
Step-by-step explanation:
Step 1: Define
[tex]\displaystyle y = \sqrt{x}(8x - 5)[/tex]
Step 2: Differentiate
[tex]\displaystyle f(x) = \sqrt{x}, \ g(x) = (8x - 5)[/tex]
Product Rule: [tex]\displaystyle y' = \frac{d}{dx}[\sqrt{x}] \cdot (8x - 5) + \sqrt{x} \cdot \frac{d}{dx}[(8x - 5)][/tex]Rewrite: [tex]\displaystyle y' = \frac{d}{dx}[x^{\frac{1}{2}}] \cdot (8x - 5) + \sqrt{x} \cdot \frac{d}{dx}[(8x - 5)][/tex]Basic Power Rule: [tex]\displaystyle y' = \frac{1}{2}x^{\frac{1}{2} - 1} \cdot (8x - 5) + \sqrt{x} \cdot 1 \cdot 8x^{1 - 1}[/tex]Simplify: [tex]\displaystyle y' = \frac{1}{2}x^{-\frac{1}{2}} \cdot (8x - 5) + \sqrt{x} \cdot 1 \cdot 8x^{0}[/tex]Rewrite: [tex]\displaystyle y' = \frac{1}{2x^{\frac{1}{2}}} \cdot (8x - 5) + \sqrt{x} \cdot 1 \cdot 8[/tex]Multiply: [tex]\displaystyle y' = \frac{8x + 5}{2x^{\frac{1}{2}}} + 8\sqrt{x}[/tex]Rewrite: [tex]\displaystyle y' = \frac{8x + 5}{2\sqrt{x}} + 8\sqrt{x}[/tex]Add/Rewrite: [tex]\displaystyle y' = \frac{24x - 5}{2\sqrt{x}}[/tex]Which of the following are not polynomials?
What does the translation rule (x - 6, y + 3) tell you to do?
translate it 6 units to the left and 3 units up
A painting has an area of 5,500 sq. cm. If the breadth of the painting is 50 cm. What is thelength of the painting?
Answer:
110 cm
Step-by-step explanation:
L= A/B (Length = Area/Breadth)
L = 5500/50
L = 110
Mark as brainliest :>
Evaluate 8^5/3
Helplpppp
Answer:
32
plz give brainliest
Step-by-step explanation:
Answer:
9.6
Step-by-step explanation:
i looked it up
Sally makes $10 per hour and a $20 bonus.
Jerry makes $9 per hour and a $50 bonus.
Which set of equations describe Sally and Jerry's income?
Any help?
Sally: 10h + 20
Jerry 9h + 50
h = hours
The mass of 1/2pint of milk is 303 g.
1 pint is 0.568 litres
1000 cm3 = 1 litre
Work out the density of the milk. Give your answer in g/cm3
The density of milk that has a mass of 303 g and volume of 1/2 pint is 1.067 g/cm³
What is an equation?An equation is an expression that shows the relationship between two or more numbers and variables
1 pint is 0.568 litres, hence:
1/2 pint = 0.568 litres per pint * 1/2 pint = 0.284 liter
1000 cm³ = 1 litre
0.284 liter = 0.284 liter * 1000 cm³ per litre = 284 cm³
Density = mass / volume = 303 g / 284 cm³ = 1.067 g/cm³
The density of milk that has a mass of 303 g and volume of 1/2 pint is 1.067 g/cm³
Find out more on equation at: https://brainly.com/question/2972832
PLEASE HURRY! I NEED HELP! THIS IS DUE TOMORROW! If you answer this I will give you brainliest!
Answer:
the answer is 3
Step-by-step explanation:
how i got this answer is........i did the round robin and i times 1 *5+4 and i got 9 so you will get 3/4 *9/5 and i got 27/9 and you will divided 9*3 and you will get 3 so that is the answer 3
i hope you did good on your test
Joni has a circular garden with a diameter of 16.5. If she uses 2 teaspoons of fertilizer for every 25 square feet of garden how many teaspoons of fertilizer will Joni need for her entire garden?
Answer:
17.106 Teaspoons of fertilizer
Step-by-step explanation:
Joni has a circular garden with a diameter of 16.5. If she uses 2 teaspoons of fertilizer for every 25 square feet of garden how many teaspoons of fertilizer will Joni need for her entire garden?
Step 1
We calculate the area of the garden.
The garden is circular in shape.
Area of a circle = πr²
r = radius = Diameter/2
Diameter = 16.5 ft
r = 16.5/2
r = 8.25 ft
Area of the circle = π × 8.25²
Area of the circle (Garden) = 213.82464998 ft²
Approximately = 212.825ft²
Step 2
If she uses 2 teaspoons of fertilizer for every 25 square feet of garden how many teaspoons of fertilizer will Joni need for her entire garden?
25 ft² = 2 teaspoons of fertilizer
212.825ft² = x
Cross Multiply
25 ft² × x = 212.825ft² × 2
x = 213.825× 2/25 ft²
x = 17.106 Teaspoons of fertilizer
The candy of a lolipop is in the shape of a sphere with a diameter of 4 cm. The
cylindrical stick inside the candy is the same height as the sphere and has a radius of
0.5 cm. What is the composite volume of the candy? Round to the nearest tenth, if
necessary.
Answer these two questions for brainiest hurry:)
-10.2 + c = -8.14 solve this equation
also Tell whether -8 is a solution of - j - 7 > -1. Show your work and answer yes or no
Answer:
C=2.06
Step-by-step explanation:
-8.14+10.2=2.06
2,6,18,54 what is the 10th term of the sequence
Answer:
78
Step-by-step explanation:
I'm really good at these
Answer:
Step-by-step explanation:
This is a geometric sequence with common ratio 3.
10th term = (4th term)×3¹⁰⁻⁴ = 54×3⁶ = 39366
HELP ME PLZZZZZZZZZZ
Answer:
In both cases, we have similar figures.
This means that the shape of the figures is the same, but the size is different:
PQST is similar to STNR and to NRPQ
VUYZ is similar to YZWX and to VUWX
this means that, for example, in problem 18, the ratio between ST and NR must be the same as the ratio between PQ and ST. This happens because the measure increases by the same scale factor.
With this in mind, we can solve the problem:
18)
ST = 7.5
NR = 5.5
Then the quotient ST/NR is:
ST/NR = 7.5/5.5
And, as we said above:
PQ/ST = ST/NR
PQ/7.5 = 7.5/5.5
PQ = (7.5/5.5)*7.5 = 10.23
19) Here we should have:
YZ/VU = WX/YZ
Then:
22.9/35 = WX/22.9
(22.9/35)*22.9 = WX = 14.98
i need your help for 10 points and maybe a crown
Answer:
288
Step-by-step explanation:
[tex]6 \times 8 \times \frac{1}{2} \times 2 + 6 \times 10 + 8 \times 10 + 10 \times 10 = 288[/tex]
Answer:
288 sq cm
Step-by-step explanation:
Hope this helps!!
Please mark brainliest.
Ted is making chocolate chip pancakes for his whole family. He wants to make 20 pancakes using a 3-cup bag of chocolate chips. How many cups of chocolate chips will be in each pancake? Write your answer as a proper fraction or mixed number.
Answer:
3/20
Step-by-step explanation:
Given: Number of cups of pancakes to be made = 20
Number of bag of chocolate chips available = 3
Therefore, cups of chocolate chips will be in each pancake= 3/20
How many times do we have to multiply 3.25 to get 13?
Answer:
4 times
Step-by-step explanation:
Answer:
4
Step-by-step explanation:
Can someone please help me solve these?
9514 1404 393
Answer:
(c) h(x) = (3x +4)(2x +1)
Step-by-step explanation:
The answer choices differ in the values they create for the last two terms of the trinomial. The last term (+4) is created by all of the choices except the first one.
The middle term (11x) is only created by the third choice:
(3x +4)(2x +1) = (3x)(2x) +(3x)(1) +(4)(2x) +(4)(1)
= 6x^2 +3x +8x +4
= 6x^2 +11x +4 . . . . matches the given h(x)
what is the slope of the line that modles the table below?
Answer:
3/4
Step-by-step explanation:
as y goes up 3 x goes up 4
I need help with all the questions you see
Answer:
1/ -6=12+1/3a
Rewrite the equation as 12+1/3a=−6.
12+1/3a= −6
Combine 1/3 and a.
12+a/3= −6
Move all terms not containing a to the right side of the equation.
a/3= −18
Multiply both sides of the equation by 3.
3⋅a/3=3⋅ −18
Simplify both sides of the equation.
a= −54
2/ -6 =12 -1/3a
Rewrite the equation as 12−13a=−6.
12−1/3a=−6
Combine a and /13.
12−a/3=−6
Move all terms not containing a to the right side of the equation.
−a/3=−18
Multiply both sides of the equation by −3.
−3⋅(−a/3)=−3 ⋅−18
Simplify both sides of the equation.
a=54
Step-by-step explanation:
if x=3 what is the value of 3x
Answer:
The answer is 9.
Step-by-step explanation:
If x equals 3 and you have 3x its basically just 3 times 3 so you get 9 as the result.
I hope this helps you :D
I WILL GIVE THE BRAIN LIST
Answer:
its g ;)
Step-by-step explanation:
trust me and please mark me brainliest the reason i know it is because well, i can barley explain it sorry have a nice day and hope this helps and please mark me brainliest thank you very much!
2/3,2/8,2/6
list from greatest to least
Simplify fully 8x2y
4xy
Will mark BRAINlIEST!!!
What is 2/7+ (−4/7)
Answer:
- 2/7
Step-by-step explanation:
+ and - becomes -
2/7 - 4/7 = - 2/7
PLEASE MARK BRAINLIEST!!! <3
Answer:
6/9 yeah that's it I looked It, up.
Step-by-step explanation:
whats the solution to this equation y=3x+7 y=-2x+3
(1,-4)
(-2,-7)
(-2,1)
(1,10)
Answer:
I love algebra anyways
The ans is in the picture with the steps how i got it
(hope this helps can i plz have brainlist :D hehe)
Step-by-step explanation:
The function f is such that f(x) = 2x/3x+5 The function g is such that g(x) = 3/x+4 Find fg(-5)
Answer:
[tex]f(g(-5)) = \frac{3}{2}[/tex]
Step-by-step explanation:
Given
[tex]f(x) = \frac{2x}{3x+5}[/tex]
[tex]g(x) = \frac{3}{x+4}[/tex]
Required
Find f(g(-5))
First, we calculate f(g(x))
[tex]f(x) = \frac{2x}{3x+5}[/tex]
Substitute g(x) for x
[tex]f(g(x)) = \frac{2g(x)}{3g(x) + 5}[/tex]
Substitute [tex]\frac{3}{x+4}[/tex] for g(x)
[tex]f(g(x)) = \frac{2*\frac{3}{x+4}}{3*\frac{3}{x+4} + 5}[/tex]
[tex]f(g(x)) = \frac{\frac{6}{x+4}}{\frac{9}{x+4} + 5}[/tex]
[tex]f(g(x)) = \frac{6}{x+4}/ (\frac{9}{x+4} + 5})[/tex]
Take LCM
[tex]f(g(x)) = \frac{6}{x+4}/ \frac{9+5x+20}{x+4}}[/tex]
[tex]f(g(x)) = \frac{6}{x+4}/ \frac{5x+29}{x+4}}[/tex]
Rewrite as multiplication
[tex]f(g(x)) = \frac{6}{x+4}* \frac{x+4}{5x+29}}[/tex]
[tex]f(g(x)) = \frac{6}{5x+29}[/tex]
Substitute -5 for x
[tex]f(g(-5)) = \frac{6}{-5*5+29}[/tex]
[tex]f(g(-5)) = \frac{6}{-25+29}[/tex]
[tex]f(g(-5)) = \frac{6}{4}[/tex]
[tex]f(g(-5)) = \frac{3}{2}[/tex]
x^2+3x-24=
x
2
+3x−24=
\,\,3x+1
3x+1
Answer:
x=8 lol this is so easyndiewkkwwkwkwkw
PLEASE STOP STEALING MY QUESTIONS OMGG
Answer:
The answer is the last one: 9,4,1
Step-by-step explanation:
- Output means y
- Input means x
The question asks to input -4, 1, 4 to find the output value
If we input -4, the answer is:
y = - x + 5
y = - (-4) + 5
y = 4 + 5
y = 9
If we input 1, the answer is:
y = -x + 5
y = - (1) + 5
y = -1 + 5
y = 4
If we input 4, the answer is:
y = -x + 5
y = - (4) + 5
y = -4 + 5
y = 1
Hope it helps!